2018
DOI: 10.1037/tra0000286
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of posttraumatic growth 10–11 months after a fatal earthquake.

Abstract: Support was found for the coping model of PTG, suggesting the importance of fostering growth to manage posttraumatic distress. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
(51 reference statements)
3
15
1
Order By: Relevance
“…Conversely, sense of mastery, self-control, or self-efficacy are resources primarily focused on problem solving in challenging times and on coping with potentially resulting distress; hence, individuals exhibiting greater levels of mastery may be less inclined to appraise their circumstances as opportunities to reap benefits from these experiences. This reasoning might be particularly compatible with theoretical and empirical voices arguing that the accounts of positive and beneficial posttraumatic experience are more illusory, thus representing primarily coping efforts aiming at justifying suffering, rather than manifesting actual psychological and social empowerment (Achterhof et al, 2018; Hobfoll, 2011; Tedeschi & McNally, 2011). Moreover, there are empirical reports that revealed significant negative correlations between mastery/efficacy and PTG indicating that people with greater beliefs in their coping competency were less likely to report positive life changes in the aftermath of crises (e.g., Moore, Cerel, & Jobes, 2015; Pooley et al, 2013).…”
Section: Personal Masterymentioning
confidence: 54%
“…Conversely, sense of mastery, self-control, or self-efficacy are resources primarily focused on problem solving in challenging times and on coping with potentially resulting distress; hence, individuals exhibiting greater levels of mastery may be less inclined to appraise their circumstances as opportunities to reap benefits from these experiences. This reasoning might be particularly compatible with theoretical and empirical voices arguing that the accounts of positive and beneficial posttraumatic experience are more illusory, thus representing primarily coping efforts aiming at justifying suffering, rather than manifesting actual psychological and social empowerment (Achterhof et al, 2018; Hobfoll, 2011; Tedeschi & McNally, 2011). Moreover, there are empirical reports that revealed significant negative correlations between mastery/efficacy and PTG indicating that people with greater beliefs in their coping competency were less likely to report positive life changes in the aftermath of crises (e.g., Moore, Cerel, & Jobes, 2015; Pooley et al, 2013).…”
Section: Personal Masterymentioning
confidence: 54%
“…Even among the few longitudinal studies, PTG is typically assessed via retrospective self‐reports of growth. The extant longitudinal studies suggest it is common for disaster survivors to perceive PTG, yet this self‐perception may be more reflective of active coping efforts than of actual positive personality change (Achterhof et al, 2018; Hafstad, Kilmer, & Gil‐Rivas, 2011; Holgersen, Boe, & Holen, 2010). For instance, studies suggest perceived PTG from disasters is predicted by deliberate cognitive processing (e.g., postdisaster meaning making) and secondary control beliefs (e.g., changing one's thoughts to accommodate one's postdisaster reality), as well as by virtues (e.g., gratitude and spiritual fortitude; McElroy‐Heltzel et al, 2018; Zhou & Wu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In so doing, we are able to examine change over time (via the longitudinal design of both studies) and examine prospective change since the disaster (via the predisaster‐inclusive design of Study 2). Lastly, most extant longitudinal studies focus on only one disaster and sample (e.g., Achterhof et al, 2018), but we have recruited samples from two major hurricanes that occurred in the same geographical region (U.S. South) and just 2 weeks apart, permitting examination of the extent to which findings replicate across similar samples. (Nonetheless, only Study 2 can address our central research question, given the lack of predisaster data in Study 1.…”
Section: Introductionmentioning
confidence: 99%
“…The constructive side is correlated with healthy adjustment, whereas the illusory side is correlated with denial. Similarly, other studies have concluded that self-reported growth can indicate an adaptive outcome of successful cognitive coping or a positive illusion that is a result of avoidance and denial (76,91). However, the question remains whether self-perception of growth may be beneficial to individuals even if it does not reflect measurable change.…”
mentioning
confidence: 99%